Is there a future for distance learning in Brazil? - Maia, Carmem (Proceedings of the International Conference on Networked Learning, 2008)
In the past, distance learning in Brazil followed a similar pattern to the rest of the world, with regard to the kind of teaching-learning offered and mainly consisted of correspondence courses. In spite of the wide dissemination of distance learning and its historical success, its methodology was always criticized on prejudicial grounds and associated with courses of a low or dubious standard. However, There has been a considerable change in this attitude in the last 15 years, with the emergence of Internet. Basically, higher education distance learning has begun to become a reality in the country on account of both the Internet and new Brazilian legislation which now allows up to 20% of the current syllabus in the Curriculum to be provided in a distance learning format using the new technology. As a result, there has been a flurry of activity - almost a revolution - in Brazilian education with the setting up of a new market for online educators. Thus, the kind of distance-learning that is having success in Brazil is that which manages to offer the best cost-benefits both for the student and for the institution which is able to attract the largest number of students at a reasonable cost. As a result, The web or e-learning that might be valuable from a pedagogical standpoint, in institutional terms, has proved to be very expensive and even elitist. This research has outlined the state of the art of distance learning in Brazil and advocates employing work-based learning as a methodological framework to introduce innovations in Distance Learning in HE, by combining the students needs and the opportunities provided by the web with the academic resources from the University.